Extended Kalman filter algorithm for continuous system parameter identification - Sinha S.K.; Nagaraja T. (My University, 2025)
An extended Kalman filter algorithm for parameter identification has been developed for continuous system. It utilises the existing procedure for continuous system state estimation and the form of discrete Kalman filter algorithm for parameter identification. Effectiveness of the new algorithm, given here, is illustrated by a second order power system and a third order attitude control problem. © 1990.